Analysis of the Motives of Indian Collector’s for Accumulating Collectibles - Kaushik, Anshul; Kaur, Dr. Ramandeep (The journal of contemporary issues in business and government, 2021)
People across the globe collect numerous items ranging from stamps, stones, letter, coins, banknotes, paintings, photographs, cultural artifacts to vintage artworks. Collection might refer to some type of assortment with which the collector has an emotional connect. Money or profit in exact business term might not even be a factor to consider for a true collector. This is the feeling or the delight of owning the items which underline the true essence of collection. Recently, there has been a substantial increase in the trade of collectible items especially in antique items resulting in generation of revenue for the nations. This has led to the emergence of another set of people who collect items for profit and investment around the globe, known as professional collectors. India, being no exception is also seeing its share of surge in international trade in collectibles.